David Cameron's Liberal Interventionism in the British Foreign Policy (2010-2016) - KADDOUR, Khadidja (My University, 2018)
Throughout the twenty-first century, Britain has witnessed the leadership of three prime ministers. This work focuses on the premiership of David Cameron and his interventions, particularly at the level of foreign affairs. When Cameron came to rule Britain was going through economic crises, he had a new approach of intervention, as it was shifted from liberal interventionism to liberal conservatism. Cameron had to take a tough decision, which allowed Britain had a powerful place in EU and the world; together with retention the stronger relationship with the world, yet some decisions had a negative side. The work is divided into three chapters. The first introduces the British foreign policy in the twenty-first century. The second one is devoted to the profile of Cameron. The last one sheds light on some major instances of interventionism practiced by Cameron. Most of the time, Cameron's interventions in the EU are economic; whereas his interventions in others parts of the world are more strategic, diplomatic and political.
Keywords: Britain; David Cameron (1910-1916); Interventionism; Liberal and Conservative; Foreign Policy